Pendidikan Holistik: Perspektif Filsafat Sufisme dalam Pengembangan Kurikulum: Holistic Education: Sufism Philosophical Perspective in Curriculum Development - Maghfiroh, Ana Minniswatil; Akhyak, Akhyak (Undiksha, 2024)
Holisitic Education is an approach to learning that encompasses social, emotional, spiritual, and moral (character) aspects. Holistic Education is considered capable of addressing the challenges in the world of education where some institutions focus solely on academics. By combining Holistic Education with Sufism, it is believed that more efficient and innovative learning can be created. This can be implemented in Islamic educational institutions in curriculum development, which is also important to be done continuously according to needs. The purpose of this research is to determine that Holistic Education can be created with a Sufism approach through curriculum development. The method used is library research, which does not require researchers to directly engage in fieldwork but rather find data through scientific writings such as journals, books, and articles. The results of this study show that Holistic Education with a Sufism approach in curriculum development can have a positive impact on students themselves, particularly in spiritual, social, and moral aspects